Crop Diversity and Cropping Patterns of Comilla Region - Saha, A; Nasim, M; Rashid, M Harunur; Shahidullah, SM (Bangladesh Rice Journal, 2018)
Comilla region is highly diverse in respect to topography, agro-ecology, land-use pattern and cropping systems. Planning of agricultural development largely depends on the reliable and comprehensive statistics of the existing cropping patterns, cropping intensity and crop diversity of a particular area, which will provide guideline to our policy makers, researchers, extensionists and development workers. The study was conducted over all 33 upazilas of Comilla region during 2016 using pre-tested semistructured questionnaire with a view to document the existing cropping patterns, cropping intensity and crop diversity. From the present study it was observed that 73.56% of net cropped area (NCA) is covered by exclusive rice cropping systems whereas deep water rice cropping system occupied 16.09% of the regional NCA. The most dominant cropping pattern single Boro alone occupied 26.18% of NCA with its distribution over 30 out of 33 upazilas. The second largest area, 19.93% of NCA, was covered by Boro−Fallow−T. Aman cropping pattern, which was spread over 25 upazilas. One hundred and forty-six cropping patterns were identified in the whole region under this investigation. The highest, 36 cropping patterns were identified in Debidwar upazila of Comilla district and the lowest, seven were in Akhura and Ashuganj of B.Baria and Comilla Adarsha upazila. The lowest crop diversity index (CDI) was reported 0.481 in Comilla Adrasha upazila followed by 0.637 in Hajiganj of Chandpur. The highest value of CDI was observed 0.964 in Haimchar of Chandpur followed by 0.956 in Muradnagar of Comilla. The range of cropping intensity (CI) value was recorded 126-292%. The maximum value was for Barura of Comilla and minimum for Hajiganj of Chandpur district. The grand mean of CDI values for Comilla region was calculated 0.935 and the average cropping intensity at regional level was 192%. Bangladesh Rice j. 2017, 21(2): 91-107